THE POLITENESS OF DIRECTIVE SPEECH ACTS IN SATU JAM LEBIH DEKAT ON TV ONE (PRAGMATIC APPROACH) - Nur Aini Syah; D. Djatmika; S. Sumarlam (Universitas Sebelas Maret, 2017)
This study aims to find out the types of directive speech act and politeness strategies used in Satu Jam Lebih Dekat talk show on TVOne. The method used in this article is descriptive method which describe the data systematically, factually, and accurately. The uninvolved conversation observation technique was used in collecting data in which this means that the present writer does not involve in the dialogues. Meanwhile, for data analysis technique, the present writer used pragmatic competence-in-dividing. The main theory of this article is the pragmatic theory of Searle’s Speech Act and Brown and Levinson’s Politeness Strategy. The results indicate that the types of directive speech act of Satu Jam Lebih Dekat program are to please, to request, to ask, to order, to invite, to forbid, to convince, to obligate, to show, to hope, to want, to warn, to advise, and to request. In addition, the politeness strategies are bald on record, positive politeness, negative politeness, and off record. The politeness of directive speech acts supports the effectiveness of talk show because of some factors such as types of directive speech act and politeness strategy. Keywords: pragmatics, directive speech act, politeness strategy, talk show